Understanding abnormal psychology - Ramsden, Pamilla (Los Angeles Sage, 2013)
This comprehensive textbook presents a thorough understanding of abnormal psychology with a focus on the integration of psychology, biology and health and is supported by interactive learning features for undergraduate students --
Keywords: Psychology, Pathological; Psychology; Mental Disorders